Action research on servant leadership: Creating an amiable work climate for all Ayala Land Premier's new property specialists - Avance, Nestor M., Jr. (Animo Repository, 2020)
Appropriation is the critical realist approach while holding a standpoint that oscillates between the extremes of positivism and constructivism, which are exactly two sides of the same coin. Through reflection and with due recognition, we appreciate these methodic shortcomings, limitations and misgivings, in resolving structural emancipatory issues that should be the hallmark of any organizational management and development. Definitely because human systems can only be changed if we could involve everybody in our process of inquiry. Therefore, it is transparent that in considering multiple variables, these system s can be controlled by the traditional method in vain. For our appreciative inquiry aims at system changes by focusing on what already works in order to gain more generative insights into pragmatically valuable leverages towards the building of behavioral facilities for transformative actions. External consultants could act as learning historians as our goals were to increase participation in dialogic discourses and reflections on past actions so as to create desirably future excellent practices. This is all practicable when documentation becomes available with the list of critical episodes so that stakeholders can appreciate the written narratives and understand our proposed actionable knowledge. In other words, Integrated Action Research is a very powerful tool for uncovering truths. Likewise, it is genuinely scientific with the emphatic observation of human systems on how behaviors can manifestly effect changes to be managed. This proves an apodicticity that with whatsoever modality we are confident about in doing our Integrated Action Research, we are also indubitably inspired by its utmost verifiability.